Mandatory and recommended immunizations. Contraindications to vaccination and adverse reaction to vaccination in the context of liability for failure to vaccinate a minor (Article 115 § 2 of the Code of Offenses.) - Ćwik-Błotnicka, Dominika; Błotnicki, Maciej (Journal of Education, Health and Sport, 2023)
Introduction: the issue of immunizations constantly raises discussion. Undoubtedly, they are an effective preventive measure and play a key role in protecting public health. However, the public still holds the view that the measles, mumps and rubella vaccine causes autism, despite numerous studies refuting its effect on the development of autism. Adverse vaccine reactions are also a cause of concern, although they are most often a mild bodily reaction. The purpose of the study: was to analyze the research problem, which is, in principle, the exclusion of liability of a person having custody of a minor for the offense of failing to vaccinate him/her with mandatory immunization in the presence of a contraindication to vaccination. The law on compulsory vaccination is discussed, taking into account the occurrence of a medical reason for non-vaccination. The scope of the subject of vaccination, adverse reaction to vaccination and contraindications to vaccination are presented. Materials and methods: databases such as PubMed and Legal Information Systems (LEX and Legalis) were searched. They relied on the Immunization Program in effect in 2023 and current criminal and medical literature and court decisions. Results: there is a collision of goods of an individual nature in the form of restriction of the right to self-determination, manifested in the obsolescence of the obligation to obtain the patient's consent to undergo a qualifying examination and immunization, with a good of a supra-individual nature in the form of public health security by ensuring the highest possible level of collective immunity. Conclusions: it is important to find a balance between the right to decide about the health of one's child and the duty to take care of public health, in order to ensure optimal results for both individuals and society as a whole.